KOMUNIKASI PERSUASIF PENYULUH AGAMA HINDU KANTOR KEMENTERIAN AGAMA KABUPATEN BADUNG DALAM MEMANTAPKAN SRADHA DAN BHAKTI UMAT HINDU - Ida Bagus Canirartha Satwika; I Dewa Ayu Hendrawathy Putri; Dewa Ketut Wisnawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The role of the Hindu Religious Counselor is very important to help the community understand and strengthen the Sradha and Bhakti teachings of Hinduism. Based on the background, three problem formulations were obtained, namely: 1) How is the Persuasive Communication Process for Hindu Religious Counselors in Badung Regency in Consolidating Sradha and Bhakti for Hindus?; 2) What is the Public Perception of the Persuasive Communication of Hindu Religious Counselors in Badung Regency in Consolidating Sradha and Bhakti of Hindus?; and 3) What are the implications of persuasive communication for Hindu religious instructors in Badung Regency in Consolidating Sradha and Bhakti of Hindus?. The theory used in this research is persuasive communication theory, constructive perception theory, and mass communication effect theory. This study uses a qualitative approach. The findings of the research are: 1) Based on the process of fostering Hindus in Badung Regency from the Persuasive Communication Aspect carried out by the Hindu Religious Counselor at the Office of the Ministry of Religion of Badung Regency, it can be divided into several stages as follows: planning, organizing, actuating, and controlling. 2) Public Perception of Hindu Religion Extension Office of the Ministry of Religion of Badung Regency in Consolidating Sradha and Bhakti, to be before and after the Application of Persuasive Communication. 3) Based on the implications are divided into 3 effects, namely: 1) cognitive effects include knowledge, affective effects include attitudes and behavioral effects include actions or behavior